Composés d'addition des halogénures de niobium(V) et de tantale(V): II. Stabilité relative des composés des chlorures avec quelques éthers, sulfures et nitriles - A. Merbach; J.-C. Bünzli (CHIMIA)
New NMR methods for the determination of relative stability constants are developed. These methods are used for the study of niobium(V) and tantalum(V) chlorides adducts with series of ethers, sulfides, and nitriles. The relative stabilities of nitriles adducts are controlled by electronic factors; however for the ethers and sulfides adducts the steric factors are more important. The sulfides adducts with NbCl5 and TaCl5 are more stable than the ethers adducts. NbCl5 is a weaker Lewis acid than TaCl5 towards ethers and nitriles; it has also a softer behaviour.